2002
DOI: 10.1104/pp.005405
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock That Controls Gene Expression in Arabidopsis Is Tissue Specific

Abstract: The expression of CHALCONE SYNTHASE (CHS) expression is an important control step in the biosynthesis of flavonoids, which are major photoprotectants in plants. CHS transcription is regulated by endogenous programs and in response to environmental signals. Luciferase reporter gene fusions showed that the CHS promoter is controlled by the circadian clock both in roots and in aerial organs of transgenic Arabidopsis plants. The period of rhythmic CHS expression differs from the previously described rhythm of chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 64 publications
8
120
0
3
Order By: Relevance
“…Thain et al . (2002) also observed period shortening in light‐grown roots of a toc1 mutant. These results are in contrast to those of James et al .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thain et al . (2002) also observed period shortening in light‐grown roots of a toc1 mutant. These results are in contrast to those of James et al .…”
Section: Discussionmentioning
confidence: 84%
“…Early work suggested that plant cells contain independent and autonomous copies of the clock (Thain et al ., 2000), although some tissue specificity of period was noted (Thain et al ., 2002). Exposure of seedling roots to LD cycles entrained them independently of shoots (Thain et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, a few examples of diurnally oscillating gene expression in roots have been reported. The genes that encode certain enzymes involved in nitrogen fixation are expressed in a diurnal pattern (Lejay et al, 1999;Abd-el Baki et al, 2000), as are the histone H1 and chalcone synthase transcripts (Corlett et al, 1998;Thain et al, 2002). Apart from the report that (A and D), as well as the ratio of the intensity of hybridization to XSP30 and rRNA (B and E).…”
Section: Diurnal Control Of Xsp30 Gene Expression In Rootsmentioning
confidence: 99%
“…However, this does not exclude the possibility of additional intercellular regulation or the existence of cell-or tissue-specific clock components (Thain et al, 2002;James et al, 2008). Additional cellbased clock studies may suggest how similarly or differently the protoplast clock functions to that of intact plants.…”
Section: The Circadian Clock In Arabidopsis Mesophyll Protoplastsmentioning
confidence: 99%